Et in Arcadia Eco: Law & Masonic Literature - Chakmakjian, Pauline (2013)
This paper explores how Umberto Eco’s novel Foucault’s Pendulum can be interpreted as a critical parody of The Holy Blood and The Holy Grail by the historians Baigent, Leigh and Lincoln respectively. We explore why two of these authors chose Dan Brown’s novel The Da Vinci Code as the object of their copyright grievance when Eco’s work was at least potentially an equal case. Especially since Eco’s work is frequently referred to as ‘the thinking man’s Da Vinci Code.’ First, we have analyzed the proximity of the structure of Eco’s novel with that of The Holy Blood and The Holy Grail’s. Second, we have highlighted the similarities between the themes in both Eco’s and Brown’s novels to show how any attempt of copyright litigation against either publication, according to the ruling of the judges in the United Kingdom’s High Court and Court of Appeal would still result in a loss for the claimants.